Health-related quality of life and the impact of dispositional life orientation in multiple sclerosis or rare neurological diseases - Krista Laakkonen; Päivi Hämäläinen; Pekka Mäntyselkä; Eila Niemi; Tomi-Pekka Tuomainen; Ari Voutilainen (Discover Public Health, 2026)
Abstract Background Health-related quality of life (HRQoL) is affected in multiple sclerosis (MS). Sense of coherence (SOC) and optimism/pessimism may be associated with HRQoL. Objective To compare HRQoL in patients with MS and rare neurological diseases (RND), and to evaluate the role of SOC and optimism/pessimism in shaping HRQoL. Methods A cross-sectional study of 905 patients (722 MS, 183 RND) recruited via the Finnish Neuro Society. HRQoL was measured with the validated Finnish version of the 15D questionnaire, SOC with the 13‑item Sense of Coherence Scale (SOC-13), and optimism/pessimism with the Life Orientation Test-Revised (LOT-R). Regression models were to assess associations between HRQoL, disease status, demographics, SOC, and optimism/pessimism. Results Mean ± SD HRQoL was higher in MS (0.79 ± 0.11) than RND (0.74 ± 0.12; Cohen’s d = 0.48; p < 0.001). RND patients scored lower in 14 of 15 dimensions, with the largest difference in discomfort and symptoms (MS: 0.66, 95% CI 0.65–0.68 vs. RND: 0.49, 95% CI 0.45–0.52; p < 0.001). Excretion-related HRQoL was lower in MS (0.63 vs. 0.70; p = 0.011). SOC showed the strongest association with HRQoL (β = 0.60), each 10-point increase associated with a 5% improvement. According to the PCA of the LOT-R, the dominant component reflected pessimism, but neither optimism nor pessimism was associated with HRQoL. Conclusion Patients with MS reported better HRQoL than patients with RND. SOC demonstrated the strongest association with HRQoL.